Circulating secretoneurin concentrations are increased in patients with acute coronary syndrome and provide prognostic information. (25th November 2020) - Myhre, P; Ottesen, A.H; Faaren, A.L; Tveit, S.H; Springett, J; Pyylampi, J; Stridsberg, M; Christensen, G; Omland, T; Rosjo, H
Abstract: Background: Secretoneurin (SN) is associated with both myocardial ischemia and cardiomyocyte Ca2+ handling, and circulating SN levels provide incremental prognostic information to established risk indices in patients with acute heart failure, acute respiratory failure, and after cardiac arrest. Purpose: To determine whether SN concentrations are increased in patients with acute coronary syndrome (ACS), and assess the prognostic value of SN among patients with suspected ACS. Methods: We included 402 patients hospitalized with chest pain at a teaching hospital and adjudicated all hospitalizations as ACS or non-ACS by two physicians working independently. Blood samples were drawn within 24 h from hospital admission and SN was measured by a novel ELISA assay. Patients were followed for mean 6.2 years and mortality was obtained from the Norwegian Cause of Death Registry. Results: SN concentrations were higher in patients with ACS (n=161 [40%]) compared to patients with chest pain without ACS (n=241 [60%]): median 32.8 (IQR 27.5–42.8) vs. 28 (24.5–34.0) pmol/L, p<0.001. The C-statistics of SN was 0.66 (95% CI: 0.61–0.71) to separate chest pain patients with ACS from chest pain patients without ACS compared to 0.82 (0.78–0.86) for high-sensitivity cardiac troponin T (hs-cTnT). Patients with ECG changes reflective of acute myocardial ischemia had higher SN concentrations (p=0.005). Sixty-five (16%) patients died during follow-up. Stratifying patients according to SN concentrations separated patients with a poor and favorable prognosis, and patients with SN in the top quartile had 4-fold higher risk of mortality compared to the patients with low SN concentrations (Figure). Higher SN concentrations were also associated with increased risk of mortality in Cox regression models, including in models that adjusted for age, sex, blood pressure, previous myocardial infarction, atrial fibrillation, and heart failure: hazard ratio 1.71 (1.03–2.84), p=0.038. The C-statistics of SN to separate patients with poor prognosis from favorable prognosis was 0.72 (0.65–0.79) and adding SN on top of hs-cTnT improved prognostication as assessed by the integrated discrimination index: 0.05±0.014, p<0.001. Conclusions: SN concentrations are increased in patients with ACS and provide prognostic information in patients with chest pain. Funding Acknowledgement: Type of funding source: Other. Main funding source(s): Akershus Unviersity Hospital, CardiNor AS